ISOLATION OF FLAVONOID FROM ANDONG LEAVES (Cordyline fruticosa (L.) A. Chev.) AND ITS ACTIVITY AS COMPLEXOR OF Fe2+ - Herlinda Djohan; Ari Widiyantoro; Anis Shofiyani (Indonesian Journal of Pure and Applied Chemistry, 2019)
Flavonoid is one of the phenolic compounds that can complex metals. One of the native plants of Indonesia which has the potential as a metal complexor is the andong plant (Cordyline fruticosa (L.) A.Chev). The isolation process to obtain pure compound are extraction, fractionation, and separation by chromatography. Chromatography method using vacuum liquid chromatography (VLC), gravity column chromatography (GCC) and preparative thin layer chromatography (TLC). This research obtained relatively pure isolate F2.8. The IR (KBr) data on wave numbers of isolate F2.8 were 3430; 2925-2855; 1749; 1609-1512; 1171 and 1100 cm-1.The result of the spectrum 1H-NMR showed flavonoid compound has similar typical spectrum of apigenin compound which showed chemical shift (δH ppm) : 6.85 (1H, s, H-3); 6.29 (1H, s H-6); 6.57 (1H, H-8); 7.03 (2H, d, J = 11.96 Hz, H-3’, H-5’); 8.03 (2H, d, J = 11.72 Hz, H-2’, H-6’). The UV-Vis (CH3OH) spectrum data of isolate F2.8 after the addition of Fe2+ showed a shift at λmax towards a greater direction with a batochromic shift which was caused a decrease in absorbance after the addition of iron (Fe2+) 20 ppm namely: 290 nm; 305 nm with respectively absorbances of 1.62 A; 0.42 A. Based on these data, isolate F2.8 is apigenin which is capable of complexing Fe2+.